Extra Loading Dose of Dexmedetomidine Enhances Intestinal Function Recovery After Colorectal Resection: A Retrospective Cohort Study - He, Guo-Zun; Bu, Ning; Li, Ya-Juan; Gao, Yuan; Wang, Ge; Kong, Zhi-Dong; Zhao, Min; Zhang, Shan-Shan; Gao, Wei (Frontiers in Pharmacology, 2022)
Importance: Postoperative gastrointestinal dysfunction (POGD) may be caused by postoperative vagus nerve tension inhibition and systemic inflammation. Dexmedetomidine (Dex) increase vagus nerve tone and afford anti-inflammatory property, which may play a role in pathogenesis. Objective: To investigate whether a higher dose of Dex enhances gastrointestinal function recovery. Design: In this retrospective study, patients receiving colorectal surgery at the First Affiliated Hospital of Xi'an Jiaotong University from 2017 to 2019 were included. We evaluated the postoperative flatus time between recipients who received loading plus maintenance dose of DEX (LMD group, 237 recipients) and those that maintenance dose (MD group, 302 recipients). Data were analyzed by logical regression, stratified, and interaction analyses. The simulated pharmacokinetics of two DEX regimens were compared using the Tivatrainer software. Thirty paired blood samples from patients whose propensity scores matched with POGD-related factors at 24 h postoperatively were randomly selected, and their tumor necrosis factor- (TNF-), cyclooxygenase-2 (COX-2), d-lactate (DLA), acetylcholine (Ach), interleukin (IL)-10, lipopolysaccharide (LPS), IL-6, and inducible nitric oxide synthase (iNOS) levels were measured. Setting: Operating rooms and general surgery wards. Participants: Among the 644 patients undergoing colorectal surgery, 12 who had colostomy, 26 without Dex infusion, 20 whose Dex administration mode cannot be classified, and 47 with a history of intestinal surgery were excluded. A total of 539 patients were included. Result: Compared with the MD group, the LMD group had shorter recovery time to flatus; lower incidences of nausea, vomiting, abdominal distension, and abdominal pain (P < 0.05); and slightly decreased heart rate. The LMD group was the independent factor of POGD (OR = 0.59, 95% CI = 0.41–0.87, P = 0.007) without being reversed in stratified and interaction analyses and had higher Dex plasma concentration from skin incision to 8 h postoperatively. The LMD group had a 39% and 43% increase in Ach and IL-10 levels, respectively, and a 33%–77% decrease in TNF-α, IL-6, COX-2, iNOS, LPS, and DLA levels (P < 0.05). Conclusion: Adding an extra loading dose of Dex can increase parasympathetic tone and decrease inflammation; hence, it can enhance postoperative gastrointestinal function recovery following colorectal surgery.